Electrospun Fibers for Recruitment and Differentiation of Stem Cells in Regenerative Medicine. Issue 12 (30th October 2017) - Sankar, Sharanya; Sharma, Chandra S.; Rath, Subha N.; Ramakrishna, Seeram
Abstract : Electrospinning is a popular technique used to mimic the natural sub‐micron features of the native tissue. The ultra‐fine fibers provide a favorable extracellular matrix‐like environment for regulation of cellular functions. This article summarizes and reviews the current advances in electrospun fiber application and focuses on the novel strategies applied for tissue regeneration and repair. It explores the different factors affecting the attachment and proliferation of mesenchymal stem cells (MSCs) on the electrospun substrates. The influence of different features of electrospun fibers in the differentiation of MSCs into specific lineages (bone, cartilage, tendon/ligament, and nerves) has been elaborated. In addition, the different techniques to mimic the hierarchical features of tissues and its effect on cellular functions are reviewed. Additionally, the new developments like three‐dimensional (3D) electrospinning, 3D spheroid double strategy and the comparative analysis of dynamic and static culture on electrospun scaffolds are discussed. With the intricate understanding of the interaction between the cells and the electrospun fiber matrix we can aim to combine the newer strategies to overcome the existing challenges and improve the potential application of electrospun fibers in the field of tissue regeneration and repair. Abstract : This review highlights the recent advances in the field of electrospun fibers for tissue engineering applications. The different modifications in the ECM engineering approach using electrospun fibers like surface functionalization, surface coating and alignment of fibers and their effect on cell proliferation, migration, and differentiation has been discussed. It elaborates the current techniques like 3D electrospinning, 3D spheroid technology, and dynamic models for tissue engineering approach as compared to the conventional static methods.